Leucocyte count is an indicator of carotid plaque instability in stroke patients - Aranđelović Minić, Gordana N (Vojnosanitetski pregled, 2017)
Background/Aim. Increasing evidence points to the inflammatory character of atherosclerosis and several parameters of inflammation have been proposed as cerebrovascular risk markers. The objective of the research was to examine the connection of serum inflammatory parameters and ultrasound (US) characteristics of the structure and size of carotid plaque. We assumed that the number of leukocytes (Le) was an indicator of carotid plaque instability and an increased risk of stroke. Methods. Serum inflammatory parameters: erythrocyte sedimentation rate in the first (ESR I) and second hour (ESR II), the number of Le, high sensitivity C-reactive protein (hsCRP) and fibrinogen were measured by standard methods. All the subjects (n = 75) were divided into 3 groups (symptomatic, asymptomatic and control). US evaluation of extracranial carotid arteries was performed in a duplex system. Plaques were classified into categories according to stenosis percentage (≥ 50%, < 50%) and pursuant to echomorphological characteristics (Gray-Weale classification). In the subjects with stroke an ischemic lesion was confirmed by computed tomography. Results. The average values of biochemical parameters in the symptomatic group were: ESR I 29.57 ± 29.87 cm, ESR II 51.60 ± 36.87 cm, the number of Le 10.10 ± 3.20 ´ 10-9 U/L, hs-CRP 8.15 ± 5.50 mg/L and fibrinogen 4.03 ± 0.70 g/L. The average values of all testing biochemical parameters in symptomatic patients were significantly higher than in the asymptomatic ones and the control group: for ESR I (p < 0.05) and ESR II (p < 0.05); for the number of Le (p < 0.001); for hsCRP (p < 0.001) and fibrinogen (p < 0.001). Category I of echomorphological characteristics in the symptomatic group was present in 66.7% of the cases and it was significantly higher than in the asymptomatic (40.0%; p < 0.05) and the control group (20.0%; p < 0.01). Univariate logistic regression analysis confirmed that all testing biochemical parameters are indicators of stroke risk. Multivariate logistic regression analysis confirmed a statistically significant correlation of the number of Le and stroke risk, while the increase in the value by a unit of measurement was associated with the growth of risk by 3.22 times (from 1.67 to 6.22). Conclusion. The number of Le is associated with the phenomenon of carotid plaque instability and may be a useful additional marker of increased risk for developing acute cerebral infarction.